Altitude training at sea level and its impact on EPO and VEGF - Mikulski, T.; Dabrowski, J.; Krzywanski, J. (Medicina Sportiva, 2014)
Introduction: Intermittent hypoxic exposure (IHE) is a no-invasive, no-pharmacological method enhancing performance, using the adaptive changes to decreased oxygen content in air. Erythropoietin (EPO) and vascular epithelium growth factor (VEGF) are very important factors in endurance sports, enhancing oxygen transport capacity and delivery to the working muscles. Objective: To evaluate, if altitude training using IHE method stimulates synthesis of both EPO and VEGF, which among many other factors are products of expression of hypoxia inducible factor. Methods: Twelve runners (age 25 ± 1 yrs, BMI 19.8 ± 0.5 kg/m2) performed IHE for one hour daily for 2 weeks. During IHE athletes breathed subsequently with hypoxic and room air according to the results of hypoxia tolerance test, total hypoxic time in one session was 35 to 40 minutes and target oxygen saturation in blood 80%. Blood samples for determination of EPO and VEGF concentrations were obtained in the morning in the fasting state before, in 5th and 14th day of IHE. Results: Blood concentration of EPO increased significantly after 4 days of IHE (from 6.7 ± 1.2 ml U/ml to 11.7 ± 0.9 ml U/ml) and remained elevated till the end of IHE (9.8 ± 0.9 ml U/ml). Also VEGF responded to IHE demonstrating the significant increase from 22.5 ± 6.0 pg/ml to 366.0 ± 49.2 pg/ml. Conclusions: Altitude training at sea level using IHE method was well tolerated by all athletes and showed positive impact on molecular level on some important factors involved in exercise metabolism. Thus, IHE can be considered as a recommended option to be combined with classic altitude training.